Trajetória da lei nº 11.645/08 e sua aplicação nas escolas - Maisa Cristina Tôrres Dantas (2021)
This research sought to describe and analyze Law No. 11.645/08, which makes the teaching of Afro-Brazilian and Indigenous History and Culture mandatory. The general objective of this investigation is to analyze the emergence, the elaboration process and the practical application of Law nº 11.645/08, with emphasis on the presence of the indigenous theme in the early years of elementary school (1st to 5th year). The research was developed throughout the years 2020 and 2021, when the SARS-CoV-2 pandemic spread. The field research had to be modified because it involved procedures that would require personal contacts. One of the criteria for reworking the initial project was the search for a safe methodological implementation that could meet the recommended sanitary measures. The research problem was resized, without abandoning the initial theme. Thus, a qualitative research was carried out, with methodological procedures that respected the protocols of social distancing. One of the research procedures used is document research and the other procedure was field research in which seven teachers were interviewed. As theoretical support, we used the “policy cycle” by the British sociologist Stephen Ball and collaborators. In order to understand the process of emergence and drafting of a law in the educational field and its application in schools. Beside that, as this is a research on the indigenous theme, decolonial studies and cultural studies were used to understand the struggles and power relations involved in issues of race and ethnicity present in the school curriculum. The data obtained from these procedures are analyzed from the perspective of critical discourse analysis. The data show advances and permanencies both in the process of drafting the law and in its practical application in schools. The advances concern the obligatory nature of the indigenous theme in the basic education curriculum. The permanencies become visible in the presence of both the legislation and the teachers' speech about the remnants of a dated vision of the original peoples.